TRACES OF HADRAMAUT’S INTELECTUALISM IN THE 20THCENTURY IN NUSANTARA ANDTHE ROLE OF ITS PESANTREN ALUMNI - Fuadi, Moh. Ashif; Kusairi, Latif; Rohmatulloh , Dawam Multazamy; Perkasa, Adrian (Jurnal Lektur Keagamaan, 2022)
ABSTRACT This research discusses the traces of Hadramaut intellectualism through the relationship of the scholarlygenealogy of Hadramaut ulamawith the 20thcentury Nusantara ulama. In addition, it analyzes thetypo-logy of Hadramaut Pesantrens and the role oftheir alumni in developing the da’wah movement in Indonesia. This research is a literature reviewstudythrough a library research approach, focusing onbooks, articles, and online news, strengthenedby interviews and field observations. This research foundthat: first, theHadramaut Pesantrenis connected through the sending of Indonesian students to Darul Musthafa, Rubath Tarim, and al-Ahgaff University;the three institutions show an inclusive character that is still suitable to be applied in Indonesia. Second, the influence of Hadramaut intellectualism can be seen through the relationship betweenthe scholarlygenealogy of Hadramaut ulamaand Nusantara ulamain the book of safinat al-najā, sulām al-taufīq, muqoddimatu al-hadromiyyah, all of which became the reference books of Nusantara ulamain compiling sharah or explanations of the book of kāsyifat al-sajā, faidh al-hijā 'alā naili al-rojā, nadzam nailul roja, kasyful hijāfī tarjamati safīnat al-najā, tanwīru al-hijā fī nadzmi safīnat al-najā,i'ā nat al-rafīq 'alā nadzmi sulām al-taufīq, inqōdzu al-ghorīq fī nadzmi sulām al-taufīq, mirqōtu al-shu'ūdi al-tashdīq fī syarhi sulām al-taufīq and mauhibatu dzi al-fadhli al-hasyīyati 'alā mukhtashor afādhol. Third, the influence of Hadramaut alumni, especially the alawiyyin circles, still has a fairly strong proselytizing influence in Indonesia after the first batch of 30 students in 1998 Darul Musthafa returned to Indonesia and developed da'wah by establishing taklim assemblies or Pesantrens. Keywords: Hadramaut, Intellectualism, Nusantara, Pesantren   ABSTRAK Penelitian ini membahas tentang jejak intelektualismeHadramautmelalui hubungan genealogi keilmuan ulama Hadramaut denganulama NusantaraAbad ke-20, dan juga menganalisis tipologipesantren Hadra-maut dan peranan alumninyadalam mengembangkan gerakan dakwah di Indonesia. Penelitian ini menggunakanpendekatanstudi pustaka (library research) melalui buku, artikel, dan berita online,diperkuat dengan wawancara dan penelusuran lapangan(observasi). Penelitian ini meng-hasilkan kesimpulan bahwa:pertama, jaringan pesantren Hadramaut ter-hubung melalui pengiriman santri Indonesia ke Darul Musthafa, Rubath Tarim, dan Universitas al-Ahgaff yang ketiga lembaga tersebut menunjuk-kan karakter inklusif yang masih cocok diterapkan di Indonesia. Kedua,pengaruhintelektualisme Hadramaut dapat dilihat melaluihubungan genealogi keilmuan ulama Hadramaut dan ulama Nusantaradalamkitab safinatal-najā,sulām al-taufīq, muqoddimatu al-hadromiyyah,yang se-muanya menjadi kitab rujukan ulama Nusantara dalam menyusun syarah atau penjelasan kitabkāsyifat al-sajā, faidh al-hijā ‘alā naili al-rojā, nadzam nailul roja, kasyful hijā fī tarjamati safīnat al-najā, tanwīru al-hijā fī nadzmi safīnat al-najā,i’ānat al-rafīq ‘alā nadzmi sulām al-taufīq, inqōdzu al-ghorīq fī nadzmi sulām al-taufīq, mirqōtu al-shu’ūdi al-tashdīq fī syarhi sulām al-taufīqdan mauhibatu dzi al-fadhli al-hasyīyati ‘alā Mukhtashor Bafādhol. Ketiga, pengaruh alumni Hadramaut terutama kalangan alawiyyinsampai saat ini masih memiliki pengaruh dakwah yang cukup kuat di Indonesia setelah 30 santri angkatan pertama tahun 1998Darul Musthafapulang ke Indonesiadan mengembangkan dakwah dengan mendirikan majelis taklim atau pesantren  Kata kunci: Hadramaut, Intelektualisme, Nusantara, Pesantren